Economically Dependent Workers: main aspects of their protection in the Spanish Labour Law and Social Security System - María Salas Porras (Italian Labour Law e-Journal, 2021)
The contribution aims at presenting the Spanish legal frame of the so called “Trabajadores Económicamente Dependientes”, putting special stress on those aspects related to both the protection given in the productive relationship by Labour Law and the one foreseen by the Social Security System.